Cognitive flexibility, central coherence and social emotional processing in males with an eating disorder. (May 2014) - Goddard, Elizabeth; Carral-Fernández, Laura; Denneny, Emma; Campbell, Iain C.; Treasure, Janet
Abstract Objectives. Females are more likely to develop an eating disorder (ED) than males. Studies of affected men may therefore inform models of risk and resilience to EDs. The aim of this study was to examine putative neurocognitive intermediate phenotypes of EDs in affected males. Methods. Cognitive flexibility, central coherence (global/detail processing), complex emotion recognition and social-threat sensitivity were investigated in men with EDs and healthy men. Measures of distress, perfectionism, and obsessive compulsivity were collected. Results. Men with EDs were more cognitively inflexible across tasks and had more difficulty integrating global information than healthy men. Unexpectedly, there were no group differences on a visuospatial task of detail processing or on social-emotional processing tasks. Men with EDs had higher scores on measures of distress, perfectionism and obsessive compulsivity than healthy men. Conclusions. Men with EDs share some of the intermediate cognitive phenotype present in women with EDs. Like their female counterparts, males with EDs show an inflexible, fragmented cognitive style. However, relative to healthy men, men with EDs do not have superior detail processing abilities, poor emotion recognition or increased sensitivity to social-threat. It is possible that gender differences in social-threat processing contribute to the female preponderance of EDs.